2010
DOI: 10.1111/j.1469-0691.2009.03036.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinical coagulase-negative staphylococci, isolated in microbiology laboratories, by matrix-assisted laser desorption/ionization-time of flight mass spectrometry and two automated systems

Abstract: A study was performed to compare matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF-MS), linked to a recently engineered microbial identification database, and two rapid identification (ID) automated systems, BD Phoenix (Becton Dickinson Diagnostic Systems, France) and VITEK-2 (bioMérieux, Marcy L'Etoile, France), for the ID of coagulase-negative staphylococci (CoNS). Two hundred and thirty-four clinical isolates of CoNS representing 20 species were analyzed. All CoNS isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 32 publications
4
83
1
6
Order By: Relevance
“…Except for S. xylosus, all tested species had a specificity of 100 %, which reinforces the utilization of low score cut-off values for species identification. S. equorum, S. piscifermentans (Dupont et al, 2010) and S. saprophyticus (Dubois et al, 2010) have been described previously to be incidentally not correctly identified by MALDI-TOF MS. Score values of up to 2.04 for misidentifications suggest that users should give more attention to critical species such as S. equorum, S. piscifermentans and S. xylosus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for S. xylosus, all tested species had a specificity of 100 %, which reinforces the utilization of low score cut-off values for species identification. S. equorum, S. piscifermentans (Dupont et al, 2010) and S. saprophyticus (Dubois et al, 2010) have been described previously to be incidentally not correctly identified by MALDI-TOF MS. Score values of up to 2.04 for misidentifications suggest that users should give more attention to critical species such as S. equorum, S. piscifermentans and S. xylosus.…”
Section: Discussionmentioning
confidence: 99%
“…A lower mean species-specific score value could also indicate a certain species where the given database could be improved. MALDI-TOF MS has been shown to be accurate in both sensitivity and specificity at the species level for staphylococci (Seng et al, 2009;Dupont et al, 2010;Szabados et al, 2012). Except for S. xylosus, all tested species had a specificity of 100 %, which reinforces the utilization of low score cut-off values for species identification.…”
Section: Discussionmentioning
confidence: 99%
“…Its value is in a rapid screening of the organism and the accessible protein pattern for characterization and distinction (Petersen et al, 2009). MALDI-TOF MS can examine the pattern of proteins detected directly from intact bacteria, giving a reproducible spectra consisting of a series of peaks corresponding to mass-to-charge ratios of ions released from bacterial proteins during laser desorption (Dupont et al, 2010). MALDI-TOF MS is considered a tool with potential to replace phenotypic identification of bacteria in clinical microbiology laboratories (Bizzini et al, 2010;Ford and Burnham, 2013;Jamal et al, 2013;Kok et al, 2013), especially due to its time-saving benefit where the extensive time needed with culture-based methods is reduced to a few minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding staphylococci, the MALDI-TOF MS has brought up an important advantage by allowing rapid and simplified identification of both S. aureus and of some species belonging to coagulase-negative staphylococci (CoNS). Unlike most commercial identification systems that allow a rapid identification of only S. aureus, the MALDI-TOF MS allows a correct identification of various CoNS species (Speers et al, 1998;Bernardo et al, 2002;Dupont et al, 2010). In a comparative study between MALDI-TOF MS and two rapid identification automated systems, BD Phoenix (BD Diagnostic Systems, France) and Vitek-2 (bioMérieux, Marcy l'Etoile, France), the identification of 234 CoNS belonging to 20 different species showed that the MALDI-TOF performance was significantly better (93.2%) than Phoenix (75.6%) and Vitek-2 performance (75.2%) (Dupont et al, 2010).…”
Section: Routine Identificationmentioning
confidence: 99%
“…Unlike most commercial identification systems that allow a rapid identification of only S. aureus, the MALDI-TOF MS allows a correct identification of various CoNS species (Speers et al, 1998;Bernardo et al, 2002;Dupont et al, 2010). In a comparative study between MALDI-TOF MS and two rapid identification automated systems, BD Phoenix (BD Diagnostic Systems, France) and Vitek-2 (bioMérieux, Marcy l'Etoile, France), the identification of 234 CoNS belonging to 20 different species showed that the MALDI-TOF performance was significantly better (93.2%) than Phoenix (75.6%) and Vitek-2 performance (75.2%) (Dupont et al, 2010). Overall, MALDI-TOF appears to be excellent at identifying various staphylococci species as demonstrated by the congruence of 99.3% (444/ 447) between MALDI-TOF and rpoB sequence-based identifications (Spanu et al, 2011).…”
Section: Routine Identificationmentioning
confidence: 99%